Resistance Training Untuk Meningkatkan Power - Muhammad Bagus Mahmudi; Danang Endarto Putro; Ridha Kurniasih Astuti (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to determine the effectiveness of the resistance training program in increasing leg power in 12 volleyball UKM athletes of STKIPPGRIPacitan. The design used was a quasi-experimental pretest–posttest with a treatment of 12 weight training sessions including squats, sumo squats, leg extensions, and calvary raises. Leg power was measured before and after treatment using a vertical jump test, then analyzed using a t-test (p<0.05). The results showed an average increase in leg power from 19.58 to 20.06 with a difference or increase of 0.55. The t-test showed a calculated p-value of 0.002<0.05, indicating that there was a difference in leg power increase after the implementation of resistance training. This indicates that resistance training exercises have an effect on increasing leg power in volleyball UKM athletes of STKIP PGRI Pacitan. The conclusion confirms that resistance training is able to increase leg power in volleyball UKM athletes of STKIP PGRI Pacitan.